(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
The given thesis makes an attempt to show the difficulties of representing near synonymy in computational lexicon base highlighting the dimensions of variation that near synonyms can present. In particular, denotational, stylistic, structural and expressive variations of near synonyms that are vital determining the differences of near synonyms are briefly overviewed to draw the conclusion on the topic. Based on the differentiation of near synonyms and conclusions drawn from them six main problems of representing near synonyms in a computational lexicon are stated. Knowledge base model that is supposed to be sufficient enough to solve the problems mentioned in the article is going to be a main topic of our further studies.